Targeted drug delivery in neurodegenerative diseases: the role of nanotechnology - Rupal Dhariwal; Rupal Dhariwal; Mukul Jain; Mukul Jain; Yaser Rafiq Mir; Abhayveer Singh; Bhavik Jain; Pankaj Kumar; Mohd Tariq; Mohd Tariq; Devvret Verma; Khemraj Deshmukh; et al. (Frontiers in Medicine)
Neurodegenerative diseases, characterized by progressive neuronal loss and cognitive impairments, pose a significant global health challenge. This study explores the potential of nanotherapeutics as a promising approach to enhance drug delivery across physiological barriers, particularly the blood–brain barrier (BBB) and blood-cerebrospinal fluid barrier (B-CSFB). By employing nanoparticles, this research aims to address critical challenges in the diagnosis and treatment of conditions such as Alzheimer’s, Parkinson’s, and Huntington’s diseases. The multifactorial nature of these disorders necessitates innovative solutions that leverage nanomedicine to improve drug solubility, circulation time, and targeted delivery while minimizing off-target effects. The findings underscore the importance of advancing nanomedicine applications to develop effective therapeutic strategies that can alleviate the burden of neurodegenerative diseases on individuals and healthcare systems.